The dislocation behaviour and GND development in a nickel based superalloy during creep. (July 2019) - Birosca, Soran; Liu, Gang; Ding, Rengen; Jiang, Jun; Simm, Thomas; Deen, Chris; Whittaker, Mark
Abstract: In the current study, dislocation activity and storage during creep deformation in a nickel based superalloy (Waspaloy) were investigated, focussing on the storage of geometrically necessary (GND) and statistically stored (SSD) dislocations. Two methods of GND density calculation were used, namely, EBSD Hough Transformation and HR-EBSD Cross Correlation based methods. The storage of dislocations, including SSDs, was investigated by means of TEM imaging. Here, the concept of GND accumulation in soft and hard grains and the effect of neighbouring grain orientation on total dislocation density was examined. Furthermore, the influence of applied stress (below and above the yield stress of Waspaloy) during creep on deformation micro-mechanism and dislocation density was studied. It was demonstrated that soft grains provided pure shear conditions on at least two octahedral (111) slip systems for easy dislocation movement. This allowed dislocations to reach the grain boundary without significant geometrically necessary dislocation accumulation in the centre of the grain. Hence, the majority of the soft grains appeared to have minimum GND density in the centre of the grain with high GND accumulation in the vicinity of the grain boundaries. However, the values and width of accumulated GND depended on the surrounding grain orientations. Furthermore, it was shown that the hard grains were not favourably oriented for octahedral slip system activation leading to a grain rotation in order to activate any of the available slip systems. Eventually, (i) the hard grain resistance to deformation and (ii) neighbouring grain resistance for the hard grain reorientation caused high GND density on a number of octahedral (111) slip systems. The results also showed that during creep below the yield stress of Waspaloy (500 MPa/700 °C), the GND accumulation was relatively low due to the insufficient macroscopic stress level. However, the regions near grain boundaries showed high GND density. At 800 MPa/700 °C (above yield at this temperature), in addition to the movement of pre-existing dislocations (SSD and GND) at a higher mobility rate, large numbers of dislocations were generated and moved toward the grain boundaries. This resulted in a much higher GND density but narrower width of high intensity GNDs near the grain boundaries. It is concluded that although GND measurement by means of EBSD can provide great insight into dislocation accumulation and its behaviour, it is critical to consider SSD type which also contributes to the strain hardening of the material. Highlights: GND accumulation in soft and hard grains and the effect of neighbouring grain orientation on local domain dislocation density were investigated. The influence of applied stress (below and above Waspaloy yield stress) during creep on deformation mechanism and total dislocation density was studied. The value and width of high-GND density near the grain boundaries are dependent on the surrounding grain orientations. High-GND width was found between hard/soft grain boundaries whereas much narrower high-GND width found between soft/soft grains was found. GND values can provide information about dislocation accumulation, it is critical however to consider SSD type which is also contributes to the strain hardening of the materials.